As relações produtivas no campo e na indústria da cana de açúcar paraibana - Lima, Roberta Oliveira Trindade de (2009)
This is a study of the productive relations in the sugarcane industry of Paraiba, in this century, emphasizing the ways to realize there holding of capital accumulation to analyze the changes arising from the restructuring of productive capital, from the year 1980, to check how they express themselves in work and life of workers of that key production to the Brazilian economy. This dissertation deals with the formatting and rearrangements triggered by the sugar cane agroindustrial capital in recent years, which are expressed within the territorial and productive and have greatly reflected in the dynamic work that develops in this segment. In the current scenario, we are faced with opening up new areas of expansion of this activity monoculture of capitalist markedly, we look for seizing and understanding the processes of exploitation of labor, embodied mainly in the sugar cane agribusiness. Also pay attention to the intensification of the precariousness of working conditions, housing and workers' lives, subject of those proceedings, under the excesses of capital, which changes in techniques of cultivation of sugarcane, not impacting on the working conditions of sugar cane. For these, the only significant change is the level of work intensification. The following text aims to show, albeit minimally, as they have been given the working relationship in the biofuels industry in general and seeks to verify the specifics of these relationships in the Northeast region of Paraíba.